TELAAH AYAT GENDER PERSPEKTIF QIRĀ’AH MUBĀDALAH DALAM AL-QUR’AN TARJAMAH TAFSĪRIYAH KARYA MUHAMMAD THALIB - Muhimmah, Faridatul (STAI AL-ANWAR SARANG, 2022)
This study examines the translation of Muhammad Talib in the Al-Qur'an Tarjamah Tafsiriyah using descriptive analytical method. The purpose of this research is to find out Muhammad Talib's translation model in interpreting several gender verses in the Qur'an and to see the influence of Muhammad Talib's ideology which is inserted in translating the Qur'an, namely the enforcement of Islamic law in Indonesia, so that it has a different point of view. own perspective on the translation of gender nuanced verses. This study uses the qirā`ah mubādalah approach that was initiated by Faqihuddin Abdul Kodir to examine the meanings used by Muhammad Talib when translating gender verses.. The results of this study confirm that the meanings of the verses translated by Muhammad Talib tend to dominate one position (bias) or ignore other roles in the relationship between men and women. The meaning of this bias is seen when Muhammad Talib interprets the implicit gender verses, namely verses that do not directly mention the subject of the verse, such as the words qawwāmūn, li al-rijāl 'alaihin darajah, nafs waḥidah is interpreted with a meaning that is more male-oriented. man. Meanwhile, other words, such as azwājan, azwāj muṭahharah, and r'īn are interpreted by women as objects, so that the reading of the Qur'an excludes women as subjects in it.